Life-Cycle Assessment Study for Bio-Hydrogen Gas Production from Sewage Treatment Plants Using Solar PVs - Hind Barghash; Zuhoor AlRashdi; Kenneth E. Okedu; Peter Desmond (Energies, 2022)
Currently, there is a global challenge of water scarcity due to climate change, rising temperatures, and other factors. One way to address this growing global challenge is by implementing technology to treat polluted water by reusing it in areas such as irrigation, cooling, and energy production, based on bio-hydrogen gas. Hydrogen gas can be produced by several methods, including dark fermentation. In this study, hydrogen gas was produced by 1L of sludge and Treated Effluent (TE) with several methods, using a reactor with a volume of 0.96 H2 L/L media. The Life-Cycle Impact Assessment (LCIA) process was used to study resource depletion, the ecosystem, and human impacts, and efforts were made to reduce the negative impacts by implementing several solutions. In this study, OpenLCA software was used as a tool for calculating the impacts, along with the ecoinvent database. Further analysis was carried out by comparing the LCIA with and without the use of solar energy. The results show that implementing hydrogen gas production with a solar energy system will help to obtain the best solution and reduce the carbon footprint, with 1.12 × 104 kg CO2 equivalent and a water depletion of 2.83 × 104 m3.